Time series analysis regression techniques - Ostrom, Charles W. (Newbury Park, Calif. ; London : SAGE, 1990)
Time series regression analysis can both explain the past and predict the future behaviour of variables. This volume explores the regression approach to the analysis of time series data. It also introduces the Box-Jenkins time series method in an attempt to bridge the gap between the two approaches.
"A SAGE university paper."
Previous ed.: 1978.
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Time-series analysis; Social sciences -- Statistical methods; Regression analysis